Case of Babesia crassa–Like Infection, Slovenia, 2014 - Strasek-Smrdel, Katja (Emerg Infect Dis, 2020)
We report a case of Babesia crassa–like infection in an asplenic patient in Slovenia in 2014. We diagnosed the infection using microscopy, 18S rRNA sequencing, and serology and monitored parasitemia using digital PCR. With its increasing occurrence, babesiosis should be included in differential diagnoses for immunocompromised patients displaying fever.